인삼농축액 발효식초의 진세노사이드 전환 및 RAW 264.7 세포에 대한 항염증 효과 - 문경은(Kyung Eun Moon); 오현화(Hyeon Hwa Oh); 정도연(Do Youn Jeong); 김영수(Young-Soo Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
인삼농축액 발효식초 제조를 위한 인삼주(GL, 1% yeast extract, 9% 에탄올, 2% 인삼농축액)에 A. pasteurianus JBA190503 균주로 제조한 종초 10%(v/v)를 첨가하고, 진탕배양(30°C, 120 rpm, 25일)하여 초산발효 하였다. 인삼식초의 발효기간(25일)에 5일 간격으로 진세노사이드 함량변화와 이화학적 특성, 유기산 및 에탄올의 함량을 분석하였다. G-Rg3와 -Rg5의 함량은 0일차에 비해 25일차에 각각 4.64배, 3.80배 증가하였다. 인삼식초는 발효 10일차 총 산도가 4.10%에 도달하였으나, 25일까지 초산발효를 지속하여 진세노사이드의 함량변화를 분석하고 발효를 종결하였다. GV의 총 산도는 6.11%, acetic acid는 6,253.01 mg%였으며 초산 전환율은 96.81%였다. RAW 264.7 대식세포에 LPS 자극으로 염증을 유도하고 세포생존율이 80% 이상 확인된 GV와 control의 1/100, 1/65, 1/50의 희석액을 처리하여 항염증 효과를 평가하였다. GV의 처리는 희석배수 의존적으로 염증 관련 인자(NO, PGE2), 전염증성 cytokine (TNF-α, IL-1β) 생성 및 염증 관련 유전자(iNOS, COX-2)의 발현을 억제시켰다. 따라서 GV의 항염증 효과는 1/50 희석배수에서 비처리구 대비 NO, PGE2, TNF-α 및 IL-1β 생성을 각각 77.37%, 21.94%, 69.17% 및 91.76% 억제하였고, iNOS 및 COX-2의 mRNA 수준에서 발현을 61.23% 및 20.59% 억제하였다. 이러한 결과를 바탕으로 A. pasteurianus JBA190503 균주로 제조된 인삼농축액 발효식초는 상업용 식초로서 품질과 안전성이 확보된 항염증 효과가 증대된 기능성 식초로 기대된다. Ginseng liqueur (GL) was prepared by adding 9% alcohol to 2% ginseng extract, and was fermented using the selected Acetobacter pasteurianus JBA190503 strain. To another GL, 10% of the seed culture was added and incubated in a shaking incubator at 30°C and 120 rpm for 25 days. The ginsenoside contents of Rg3 and Rg5 in the ginseng extract vinegar (GV) were 55.58 μg/mL and 28.52 μg/mL, respectively, which were more than four times that of GL. The changes in the ginsenoside contents and physicochemical properties (soluble sugar content, pH, total acidity, and organic acid) of the ginseng extract were evaluated during the acetic acid fermentation period. On the 10th day of fermentation, the total acidity increased to 4.10% and reached 6.41% on the 25th day. Acetic acid was identified as a major organic acid and its content was increased to 6,253.01 mg% on the 25th day from 246.05 mg% on the starting day. The anti-inflammatory effect on lipopolysaccharide (LPS, 1 µg/mL)-induced inflammatory reactions in RAW 264.7 cells demonstrated that treatment with GV decreased NO, PGE2, TNF-α and IL-1β production in RAW 264.7 cells by 77.37%, 21.94%, 69.17%, and 91.76%, respectively, and GV inhibited the activation of iNOS and COX-2 gene expression by 61.23% and 20.59%, respectively, at a 1:50 dilution. Based on these findings, the A. pasteurianus JBA190503 strain could be a suitable strain for the industrial fermentation of ginseng in ginseng vinegar production with an enhanced anti-inflammatory effect by increasing the production of low molecular ginsenosides and acetic acid. KCI Citation Count: 3